Soil aggregates stability as indicator of soil crust susceptibility in southern Mali using different methodological approaches - Jimenez, Paul Andres Jimenez; Severo, Eduardo Medeiros; Serafim, Milson Evaldo; Medeiros, Beatriz Macêdo; Silva, Bruno Montoani; Avanzi, Junior Cesar; Marques, João José; Cisse, Adama; Diakite, Moro; Curi, Nilton; Silva, Marx Leandro Naves (Geoderma Regional, 2025)
Soil surface crusting is a major constraint to agricultural productivity and hydropedological functioning. Soils in the Sahel region of West Africa are particularly vulnerable to soil crust formation due to the disintegration of soil aggregates and detachment of particles under high-intensity rainfall events. Consequently, aggregate stability serves as a key diagnostic attribute for evaluating crusting susceptibility. This study aimed to assess the relationships among soil aggregate stability, physicochemical properties, and the Crusting Susceptibility Index (CSI) in agricultural and native savanna soils from the villages of Siani and Bandiagara II, located in the Sikasso District of southern Mali. Aggregate stability was quantified using three complementary methodologies: (i) wet sieving to determine the Geometric Mean Diameter (GMD), Mean Weight Diameter (MWD), and Wet Aggregate Stability (WAS); (ii) the High Energy Moisture Characteristic (HEMC) method to calculate the Stability Ratio (SR); and (iii) a clay dispersion protocol to derive the Clay Dispersion Index (CDI). Results showed that native savanna soils exhibited superior structural stability (GMD_pm: 4.3 mm; MWD_pm: 4.5 mm; WAS: 92 %; SR: 0.4; CDI: 35 %) and lower crusting susceptibility (CSI: 0.5) compared to agricultural soils (GMD_pm: 2.9 mm; MWD_pm: 4.0 mm; WAS: 62 %; SR: 0.2; CDI: 55 %; CSI: 1.4). Aggregate stability indices (GMD, MWD, WAS, SR) were positively associated with aggregation-enhancing attributes such as total organic carbon (TOC) and cation exchange capacity (CEC), while CDI exhibited negative correlations. Furthermore, CSI was positively correlated with fine sand and coarse silt, and negatively with clay content, TOC, and CEC. A strong and significant positive correlation was found between CSI and CDI (R2 = 0.49, P ≤ 0.001), indicates that factors which promotes clay dispersion also increase crusting susceptibility, whereas the other indices showed weaker and negative correlations. Conservation management practices—such as cover cropping, crop residue retention, and control of overgrazing—are essential to enhance aggregate stability and mitigate soil crust formation in these vulnerable landscapes. In addition, to improve the predictive reliability of CSI, we recommend conducting separate assessments for agricultural and native soils, expanding the sampling framework to include a wider range of soil types, and incorporating alternative methodologies such as rainfall simulation and ultrasonic dispersion. [Display omitted]